2008
DOI: 10.3989/collectbot.2008.v27.2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic characterization of some representatives of the subgenera <i>Artemisia</i> and <i>Absinthium</i> (genus <i>Artemisia</i>, Asteraceae)

Abstract: A molecular cytogenetic study has been performed in three species of the genus Artemisia, complementing previous works on two subgenera that had been scarcely studied from this standpoint, Artemisia (A. chamaemelifolia, A. vulgaris) and Absinthium (A. absinthium). Chromomycin A 3 and 4',6-diamidino-2-phenylindole (DAPI) banding have been carried out, as well as fluorescent in situ hybridization (FISH) of 5S and 18S-5.8S-26S ribosomal DNA. Morphometrical data of karyotype characters were calculated and idiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
5
10
0
Order By: Relevance
“…The number of co-localised sites varied between four and six in A. absinthium and A. tridentata, respectively. This is consistent with previous molecular cytogenetic research to species in subgenera Tridentatae and Absinthium from Artemisia (Torrell et al 2003;Garcia et al 2007;Pellicer et al 2008). Southern hybridisation suggested that there may be some regions of the locus that are enriched in 5S rDNA sub-units (e.g.…”
Section: Characterisation Of Inter-genic Regionssupporting
confidence: 91%
“…The number of co-localised sites varied between four and six in A. absinthium and A. tridentata, respectively. This is consistent with previous molecular cytogenetic research to species in subgenera Tridentatae and Absinthium from Artemisia (Torrell et al 2003;Garcia et al 2007;Pellicer et al 2008). Southern hybridisation suggested that there may be some regions of the locus that are enriched in 5S rDNA sub-units (e.g.…”
Section: Characterisation Of Inter-genic Regionssupporting
confidence: 91%
“…Molecular phylogenetic studies, based on the analysis of chloroplast (cpDNA) and nuclear ribosomal (nrDNA) sequences have helped elucidating the systematic relationships within Artemisia, although important questions remain unresolved. Despite some differences, there is a close phylogenetic relationship between Artemisia and Absinthium, which is consistent with the available molecular phylogenies presenting species of the subgenera Artemisia and Absinthium intermixed (Pellicer et al, 2008).…”
Section: Essential Oilssupporting
confidence: 86%
“…Physical mapping of both 5S and 45S rDNAs has been carried out in some species of the genus Artemisia of the family Asteraceae, and interestingly shown that the 5S rRNA gene loci are co-localized with the 45S rRNA gene loci at the end of short arms of several chromosomes (Torrell et al 2003, Hoshi et al 2006, Garcia et al 2007, Pellicer et al 2008. In contrast, no data on the FISH with the Arabidopsis-type (T 3 AG 3 ) telomere sequences is available in the genus Artemisia.…”
mentioning
confidence: 99%